1993
DOI: 10.1109/69.204087
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting knowledge and transferring it effectively to a knowledge-based system

Abstract: The knowledge acquisition bottleneck impeding the development of expert systems is being alleviated by the development of computer-based knowledge acquisition tools. These work directly with experts to elicit knowledge, and structure it appropriately to operate as a decision support tool within an expert system. However, the elicitation of expert knowledge and its effective transfer to a useful knowledge-based system is complex and involves a diversity of activities. This paper illustrates the complete develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…This knowledge must be acquired: either deduced from physical laws, from designers in person or induced from analysis of previous designs. This knowledge acquisition is a known bottleneck for developing expert systems (Gaines and Shaw, 1993), and by extension design support tools. Methodologies have been developed to acquire design knowledge from domain experts, but this tends to be highly tailored to the particular domain under review (Hughes et al, 2001).…”
Section: Knowledge Acquisitionmentioning
confidence: 99%
“…This knowledge must be acquired: either deduced from physical laws, from designers in person or induced from analysis of previous designs. This knowledge acquisition is a known bottleneck for developing expert systems (Gaines and Shaw, 1993), and by extension design support tools. Methodologies have been developed to acquire design knowledge from domain experts, but this tends to be highly tailored to the particular domain under review (Hughes et al, 2001).…”
Section: Knowledge Acquisitionmentioning
confidence: 99%
“…However they are also time-consuming tasks. AI researchers who have been interested in eliciting qualitative knowledge detained by the experts, know the difficulties of this task [11]. Therefore expert intervention must remain limited, and be guided to be efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Our early studies in the 1980s targeted expert system shells as inference engines (Gaines and Linster, 1990) and found that many extraneous structures had to be added to manage what was not logically well-founded inference (Gaines and Shaw, 1993). With the development of logical foundations for KL-ONE semantic network systems (Brachman, 1977), leading through various implementations to the well-defined CLASSIC specification (Borgida, et al, 1989), it became attractive to target logically sound knowledge representation systems, and we implemented a formal visual language (Gaines, 1991b) for the semantics of CLASSIC, and a knowledge representation server, KRS, that was a modular, extensible, C++ implementation of CLASSIC based on an algebraic model of the logical semantics (Gaines, 1993).…”
Section: Introductionmentioning
confidence: 99%